2022
DOI: 10.3390/metabo12040304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Links between Lamb Feed Efficiency and Rumen and Plasma Metabolomic Data

Abstract: Feed efficiency is one of the keystones that could help make animal production less costly and more environmentally friendly. Residual feed intake (RFI) is a widely used criterion to measure feed efficiency by regressing intake on the main energy sinks. We investigated rumen and plasma metabolomic data on Romane male lambs that had been genetically selected for either feed efficiency (line rfi−) or inefficiency (line rfi+). These investigations were conducted both during the growth phase under a 100% concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The same trend was also observed for the other two BCAAs, leucine and valine, which tended to differ between RFI phenotypes, regardless of the feeding level (raw P values < 0.10; data not shown). This confirms results reported by others in beef cattle 11,14,16 and growing lambs 34 , showing lower plasma concentrations of BCAAs in efficient RFI individuals. Our findings, even though they did not reach statistical significance after false positive correction, align with previous conclusions obtained in a meta-analysis of genome-wide association studies in beef cattle 18 , where BCAA degradation was identified as the only metabolic pathway associated with RFI.…”
Section: Pearson Correlation Coefficient P Valuesupporting
confidence: 92%
“…The same trend was also observed for the other two BCAAs, leucine and valine, which tended to differ between RFI phenotypes, regardless of the feeding level (raw P values < 0.10; data not shown). This confirms results reported by others in beef cattle 11,14,16 and growing lambs 34 , showing lower plasma concentrations of BCAAs in efficient RFI individuals. Our findings, even though they did not reach statistical significance after false positive correction, align with previous conclusions obtained in a meta-analysis of genome-wide association studies in beef cattle 18 , where BCAA degradation was identified as the only metabolic pathway associated with RFI.…”
Section: Pearson Correlation Coefficient P Valuesupporting
confidence: 92%
“…Feed efficiency is a critical factor in reducing the costs associated with livestock production and enhancing environmental protection (31). RFI serves as a commonly employed metric for assessing feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in meat production, FCR is calculated as the amount of feed required to produce 1 kg of meat. A lower FCR indicates higher feed efficiency [27]. There are different FCR values for different sheep products as shown in Table 1.…”
Section: Feed Use Efficiencies For Sheep Productsmentioning
confidence: 99%